Информационная модель создания интерактивных должностных инструкций - Гуца, О. Н.; Довгопол, Н. В. (ХНУРЭ, 2014)
An Employment Position Instruction (Regulations) is the major tool in today's business. The existing Method of development of Regulations in the form of the text makes mistakes or the Regulations turn out difficult for studying. The report describes the Information Model of creation of On-line Employment Position Instruction which eliminates the specified defects
Keywords: информационная модель; должностные инструкции